2018
DOI: 10.1007/s12652-018-0766-7
|View full text |Cite
|
Sign up to set email alerts
|

Flexible network management and application service adaptability in software defined wireless sensor networks

Abstract: The need for highly responsive and adaptable computing systems is essential in today's network computing age. This is principally due to the drastic evolution in broad computing platforms operating at highly descriptive and abstracted mediums such as; reconfigurable computing systems, smart automation systems, cognitive and parallel programming systems which communicate using very complex resources or modes. Hence, such systems must incorporate the best forms of technologies to cater for the rapidly growing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Reconfigurable computing systems, intelligent automated systems, and cognitive and parallel programming systems that use very complex resources or patterns for communication require a well-structured and carefully implemented system. Modieginyane, Malekian, and Letswamotse implemented a software-oriented networking environment through a software-defined wireless sensor network (SDWSN) approach combined with discrete event, simulation (DES), and a highly scalable software-defined network (SDN) controller [ 3 ]. Mykhaylenko, Waehrens, and Slepniov discussed operational strategies related to the link between configuration and capabilities, especially with regard to internationalization [ 4 ].…”
Section: Related Workmentioning
confidence: 99%
“…Reconfigurable computing systems, intelligent automated systems, and cognitive and parallel programming systems that use very complex resources or patterns for communication require a well-structured and carefully implemented system. Modieginyane, Malekian, and Letswamotse implemented a software-oriented networking environment through a software-defined wireless sensor network (SDWSN) approach combined with discrete event, simulation (DES), and a highly scalable software-defined network (SDN) controller [ 3 ]. Mykhaylenko, Waehrens, and Slepniov discussed operational strategies related to the link between configuration and capabilities, especially with regard to internationalization [ 4 ].…”
Section: Related Workmentioning
confidence: 99%
“…Their paper emphasized the importance of adopting SDN in WSN networks, introduced the typical SDWSN architecture, reviewed some contributions to the SDWSN architecture and functions, and analyzed and compared goals, architectural designs, and useful functions to ensure improved WSN. Modieginyane et al 15 implemented a software‐defined WSN approach coupled with discrete event simulation (DES) and software‐defined networking controller OpenDayLight (ODL). They proposed a software‐oriented network environment to increase network service adaptability and simplify network management.…”
Section: Related Workmentioning
confidence: 99%
“…Some of the researchers suggested that the SDN is an encouraging technology for the management of sensor networks in form of energy efficiency [51]. Hence, by preventing the unnecessary loads while transmission can improve energy efficiency [52]. Proposed a solution for security that is implemented on the controller of OpenFlow.…”
Section: B Challenges In Sdwsnmentioning
confidence: 99%